Pharmacokinetics and pharmacogenomics of β-lactam-induced neutropenia. (April 2016) - Hahn, Andrea; Fukuda, Tsuyoshi; Hahn, David; Mizuno, Tomoyuki; Frenck, Robert W; Vinks, Alexander A
Aim: Determine if individuals with β-lactam induced neutropenia have polymorphisms that impair function of MRP4 or OAT1/OAT3.Methods: Subjects with β-lactam induced neutropenia were compared to controls for the presence of MRP4 and OAT1/OAT3 polymorphisms, estimated plasma trough concentrations and area under the curve.Results: Subjects with a homozygous polymorphism at MRP4 3348 A to G were 5.3 times more likely to develop neutropenia (p = 0.171). No statistical differences were noted in pharmacokinetic parameters. Contingency analysis of children greater than 5 years of age showed neutropenia in subjects who were homozygous wild type at MRP4 3348 A to G was significantly associated with standard or high dosing (p = 0.03).Conclusion: MRP4 3348 A to G should be further studied for potential contribution to the development of β-lactam induced neutropenia.